Intellectual capital and information asymmetry: recent evidence from Nigerian economy - Anifowose, Mutalib; Abdul Rashid, Hafiz Majdi; Annuar, Hairul Azlan (Universiti Malaysia Sabah, 2016)
The aim of this study is to examine the value relevance of intellectual capital by analyzing the relationship between intellectual capital (IC) disclosure and information asymmetry of listed firms on main board of Nigerian Stock Exchange. This study applies signalling theory in formulating hypothesis that guides the results analysis. By employing a two-step dynamic system generalized method of moments, and controlling for the possible endogeneity effect on the parameters estimated for a sample of 91 listed firms, this study examines the relationship between quality of IC disclosure and information asymmetry using data over the period of 2010 to 2014 financial years. The results show a significant negative association between overall IC disclosure and information asymmetry. This study recommends that management should be concerned with the adequate disclosure of IC related information as it affects the capital market activities and investors’ investment decisions. The study is first to consider the IC disclosure study across all sectors in the Nigerian economy using two-step system generalized method of moment.